Formulation of Appropriate Laws: A New Integrated Multidisciplinary Approach and an Application to Electronic Funds Transfer Regulation - White, Paul F. (Springer, 2017)
Chapter 1. Introduction . Chapter 2.The EFT System and Regulatory Framework . Chapter 3. An Integrated Multi-Disciplinary Approach ...